Principles of Islamic Education Learning According to Sheikh Yusuf Al Qardhawi and Their Relevance to UNESCO Principles - Samsirin; Syarifah; Nurul Salis Alamin; Alwi Yusron (al-Afkar, Journal For Islamic Studies, 2023)
Yusuf Al-Qardhawi, an Egyptian cleric explains in his book entitled Al-Ilmu wa Ar-Rasul about the basic framework of teaching methods. Namely about what an educator must do to create successful learning activities and produce students with character. This book explains that Rasulullah SAW was the best first teacher. Educators should make Rasulullah SAW a role model in terms of teaching ethics, what an educator must do and the characteristics of an educator in accordance with the teachings of Rasulullah SAW. The basic principles of teaching inherited by Rasulullah SAW have a close relationship with character-based learning management in schools and in other scientific institutions. If the teacher can organize everything in the learning process and can implement the basic principles of teaching that were exemplified by Rasulullah SAW in teaching, then a harmonious learning atmosphere will be created between the teacher and students, the teacher can understand his students. , it is easy for students to digest what is conveyed by the teacher which ultimately can produce graduates who are faithful, pious, accomplished and have character.